2009
DOI: 10.1021/om9005615
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Cyclopalladated Complexes with Lithium Diphenylphosphide

Abstract: Reactions of the cyclopalladated dimer {Pd(η2-L1)(μ-Cl)}2 (7) derived from N,N-dimethylbenzylamine (HL1) with lithium diphenylphosphide were studied under varied conditions. The LiPPh2 reagents used were purchased from Sigma-Aldrich Co. or synthesized from PPh3, ClPPh2, or HPPh2 by known general methods. Depending on the source of lithium phosphide, solvent, and reagent ratio, reactions of LiPPh2 with complex 7 resulted in the formation of different products. The commercial LiPPh2 solutions reacted with compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 69 publications
1
25
0
Order By: Relevance
“…The isolation of free preligands was previously reported in KPPh 2 reactions with CPCs containing an (sp 2 )CePd bond [13] as well as in the Pd-catalyzed phosphination reactions of aryl triflates with PPh 3 [26]. The formation of such products can be explained by b-hydride elimination of the alkoxide-containing Pd(II) intermediate, which could be formed after the adventitious cleavage of a CeO bond in THF by the phosphide [11,13].…”
Section: Kpph 2 Reactions Of Cpcs With An (Sp 3 )Cepd Bondmentioning
confidence: 83%
See 2 more Smart Citations
“…The isolation of free preligands was previously reported in KPPh 2 reactions with CPCs containing an (sp 2 )CePd bond [13] as well as in the Pd-catalyzed phosphination reactions of aryl triflates with PPh 3 [26]. The formation of such products can be explained by b-hydride elimination of the alkoxide-containing Pd(II) intermediate, which could be formed after the adventitious cleavage of a CeO bond in THF by the phosphide [11,13].…”
Section: Kpph 2 Reactions Of Cpcs With An (Sp 3 )Cepd Bondmentioning
confidence: 83%
“…Previously, we showed that both LiPPh 2 and KPPh 2 are capable of reacting with dimeric chloro-bridged CPCs [11,12]. However, the outcome of the LiPPh 2 reactions with CPCs was highly sensitive to the phosphide structure in the solution, which in turn, depended on the preparation method, concentration and age of the chemical.…”
Section: Kpph 2 Reactions Of Cpcs With An (Sp 3 )Cepd Bondmentioning
confidence: 99%
See 1 more Smart Citation
“…Reactions at the C-Pd bond of cyclopalladated complexes (CPCs) [1][2][3][4][5] (e.g., phosphination [6][7][8][9][10], chlorination [11][12][13][14], iodination [15][16][17][18][19], bromination [15,16], acetoxylation [20][21][22][23][24][25] and other transformations [15,[26][27][28][29][30][31]) represent an attractive method for highly regioselective functionalization of organic compounds. These Pd-mediated transformations are gaining importance as a synthetic method, providing access to new organic and organometallic compounds not readily available by other methods.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] Although a wide variety of transition-metalcatalyzed reactions for functionalizing CÀH bonds are currently available, examples of carbon-phosphorus bond formation are significantly limited, presumably owing to the strong coordinating character of phosphorus reagents. [3,4] Existence of an excess amount of coordinative phosphorus over metal in a reaction media would hamper a process to activate less coordinative CÀH bonds. Very recently, Yu and co-workers reported a pyridine-directed CÀH phosphonation reaction catalyzed by palladium, in which H-phosphonates were directly used.…”
mentioning
confidence: 99%